Advances in physical organic chemistry. - Williams, Ian H.; Williams, Nicholas H. (Academic Press, 2017)
Advances in Physical Organic Chemistry, Volume 51, the latest release in the series, is the definitive resource for authoritative reviews of work in physical organic chemistry. It provides a valuable source of information for not only physical organic chemists applying their expertise to both novel and traditional problems, but also for non-specialists across diverse areas who identify a physical organic component in their approach to research. Its hallmark is a quantitative, molecular level understanding of phenomena across a diverse range of disciplines.